Kajian Ketahanan Masyarakat yang Terdampak Banjir Rob di Wilayah Pesisir Kabupaten Pekalongan - Erlis Caesar Reviana; Iwan Rudiarto (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Indonesia has many village resilience developed in various districts and cities, including one in Pekalongan Regency, namely in Wonokerto Regency. The impact of climate change that is sustainable and determines the lives of rural communities, special strategies are needed to shape community resilience in the face of disasters, namely flooding. Adaptation carried out by the local community is to raise houses and roads to reduce the entry of water into the house. The purpose of this study is to assess the level of resilience of rural communities facing tidal flooding in coastal areas. Bearing in mind the catastrophic events due to climate change on the availability of land resources that affect the ecological conditions of the environment, economy, and social communities and infrastructure in the study area. the research method used is a quantitative method with analytical tools such as Geographic Information Systems and community resilience calculation. The results of a community resilience study conducted found that people in the coastal areas of Wonokerto Subdistrict were in a low economic condition with a score of 0.39, this is because most of the people working depend on the area. It is hoped that the government can be more sensitive to provide assistance to people who really need help.